Adaptation and Validation of the Spanish Version of the Instrument to Evaluate Nurses’ Attitudes Toward Communication With the Patient for Nursing Students - Giménez-Espert, María del Carmen; Maldonado, Sandra; Pinazo, Daniel; Prado-Gascó, Vicente (Frontiers in Psychology, 2021)
Communication is essential to quality of care and patient satisfaction. It has been linked to positive patient outcomes, increased engagement, improved health outcomes and safe practices. Given these benefits and the association between attitudes and behaviours, as behaviours can be predicted by studying attitudes, assessing nursing students' attitudes toward patient communication is critical as future nursing professionals. For this purpose, the main aim of this study was to adapt and validate an instrument to measure nurses´ attitudes towards communication (ACO) for nursing students. The attitudes towards communication with patients were analyzed. Then, differences in the dimensions of the instrument (ACO) for nursing students according to academic course, and the correlations were calculated. A cross-sectional study was carried out in a convenience sample of 1417 nursing students from five universities in Valencian Community (Spain) during the 2018/2019 academic year, 83.8% (1187) were women. The reliability was analyzed, using the Cronbach’s alpha and composite reliability (CR). Analysis of construct validity was performed with exploratory factorial analysis (EFA) and confirmatory factorial analysis (CFA). The instrument adapted from nurses to nursing students was composed by 25 items grouped in three dimensions: affective, cognitive and behavioural. The psychometric properties suggested that the instrument ACO for nursing students, was reliable and valid. The nursing students´ attitudes towards communication were positive with high levels in cognitive and behavioural dimensions, while scores were worst in the affective component. The second year nursing students showed more positive attitudes in the affective dimension, while in the cognitive and behavioural dimension the most positive attitudes were found in the first year. In the correlations, the behavioural and cognitive dimension showed a significant, positive and very high correlation. These findings should be considered in developing academic plans to improve students’ effectiveness of the communication education process to increase the quality of patient care and well-being of nursing students.